P204 Serodiscordance and sex partner concurrency: evidence for racial disparities in HIV among gay and bisexual men (MSM). (14th July 2019) - Tilchin, Carla; Schumacher, Christina; Ghanem, Khalil; Hamill, Matthew; Rompalo, Anne; Fields, Errol; Latkin, Carl; Greenbaum, Adena; Jennings, Jacky
Abstract : Background: There are extreme racial disparities in HIV infection among MSM in the U.S. These disparities may in part be explained by racial differences in the transmission potential (i.e. mixing between infected and uninfected individuals) and structure (i.e. density) of sexual networks. The objective was to determine whether the association between HIV serodiscordance and sex partner concurrency differed by race among MSM sex partner dyads. Methods: Data came from the Understanding Sexual Health in Networks Study, an ongoing longitudinal cohort among MSM ages 18–45. Participants completed an egocentric sexual network survey with questions about 3 most recent sex partners in the past 3 months. An HIV serodiscordant partnership was defined as a dyad with a positive status index and a negative or unknown status partner or vice versa. Summary statistics, chi-squared tests, and logistic regressions adjusted for the nested structure of the data were used for hypothesis testing. Results: 163 MSM reported on 354 (median: 3, range: 0–3) sex partnerships. MSM were 63.2% Black (BMSM), on average 29.4 (SD 5.96) years old, and 33.6% reported condom use at last sex. There were no differences in age or condom use by race. Among partnerships, index BMSM (vs. non-BMSM) were more likely to report serodiscordant partnerships (48.8% vs. 14.4%, p-value<0.001) but not sex partner concurrency (87.4% vs. 77.8%, p-value 0.29). Among BMSM, sex partner concurrency was significantly associated with 4.97 higher odds (95% CI: 2.26, 10.91) of having a serodiscordant partnership, and this association was not significant among non-BMSM. Conclusion: Among BMSM dyads, we found evidence of the necessary and sufficient causes for HIV transmission including mixing between infected and uninfected individuals (i.e. serodiscordance) combined with dense sexual network structures (i.e. sex partner concurrency) and we did not find this evidence among non-BMSM dyads. These factors may help explain persistent racial disparities in HIV. Disclosure: No significant relationships.